EKSPRESI NILAI ISLAM MELALUI SENI: PEMBELAJARAN SKI MELALUI TEATER ISLAMI SEBAGAI BENTUK EKSPRESI SENI DALAM PEMBELAJARAN PAI-BP DI SMK TELKOM PURWOKERTO - Azkia Faiqotun Ni’mah; Sunhaji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research explores the effectiveness of Islamic Cultural History (SKI) learning through Islamic Theater as a form of artistic expression within the Islamic Religious Education and Character Building (PAI-BP) subject at SMK Telkom Purwokerto. The background of this study is the need for innovative and relevant learning methods, considering the importance of Islamic values in shaping student character. Islamic Theater offers a multidimensional approach that not only conveys historical information cognitively but also internalizes moral and spiritual values through aesthetic experience. The research employed a descriptive qualitative method, with data collection through participatory observation, in-depth interviews with PAI-BP teachers and students, and document analysis related to the curriculum and student theater productions. Research subjects included teachers and tenth-grade students at SMK Telkom Purwokerto involved in SKI learning through Islamic Theater. The findings indicate that the use of Islamic Theater in SKI learning successfully enhanced students' understanding of Islamic historical concepts, appreciation of Islamic values, and artistic expression skills. Students demonstrated high enthusiasm, active involvement, and the ability to interpret and reflect on Islamic teachings through the medium of theater. Furthermore, Islamic Theater also proved capable of developing students' collaboration, creativity, and self-confidence. This research recommends Islamic Theater as an effective and innovative learning model for integrating religious education and art, and as a means of strengthening Islamic character in the school environment.